PEMBELAJARAN BERBASIS MASALAH MENGGUNAKAN POHON MATEMATIKA TERHADAP HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR SISWA - Fatimah fatimah; Nurhidayah Nurhidayah (Universitas Sulawesi Barat, 2018)
This study aims to describe the effect of problem-based learning models in mathematical tree media on students' mathematics learning outcomes in terms of students’ learning motivation. The study was conducted in SMP Negeri 5 Wonomulyo. The population was class VII consisted 144 students of 7 classes. The sample was 44 students of class VII B (experiment class) and class VII C (control class). The instrument was used a questionnaire for student learning motivation and learning outcomes test. Data analysis used descriptive and inferential statistical analysis. The results showed that descriptively the average value of students 'mathematics learning outcomes in the experimental class with high motivation was greater (86, 67) from the control class (80.5), as well as low motivation showed that the average value of students' mathematics learning outcomes in the larger experimental class (81.5) from the control class (77.8). In inferential, it is found that there is no interaction between problem-based learning models and mathematical tree media with learning motivation on students' mathematics learning outcomes. Students with high motivation, there was no significant effect on the application of problem-based learning models in mathematical tree media on students' mathematics learning outcomes. Unlike the case with students with low motivation, significantly influence the application of problem-based learning models in mathematical tree media on student learning outcomes.